Frequency-Domain Physical-Parameter System Identification of Building Structures with Stiffness Eccentricity - Nabeshima, Kunihiko; Takewaki, Izuru (Frontiers in Built Environment, 2017)
A frequency-domain method of physical-parameter system identification is developed for three-dimensional building structures with stiffness eccentricity. Equations of motion in the time domain are transformed into the frequency domain. The dynamic equilibrium of the free body above the j-th story is used to identify the j-th story stiffness and damping. It is required to measure the horizontal and rotational accelerations at all stories to identify the story stiffness and damping coefficients of all stories. Compared to the previous approach using the special identification function, the limit manipulation at zero frequency is unnecessary and is robust for noise. Furthermore, it should be remarked that the quantities of eccentricities in all stories can be identified using the slopes of the functions for torsional stiffness identification in the frequency domain.